2019
DOI: 10.4014/jmb.1906.06030
|View full text |Cite
|
Sign up to set email alerts
|

Ralstonia pickettii enhance the DDT biodegradation by Pleurotus eryngii

Abstract: DDT is a hydrophobic organic pollutant, which can be bio-accumulated in nature and have adverse consequences on the physical condition of humans and animals. This study investigated the relationship between the white-rot fungus Pleurotus eryngii and biosurfactantproducing bacterium Ralstonia pickettii associated with the degradation of DDT. The effects of R. pickettii on fungal development were examined using in vitro confrontation assay on a potato dextrose agar (PDA) medium. R. pickettii culture was added to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 67 publications
(90 reference statements)
0
17
2
Order By: Relevance
“…Mixed cultures have been inspected to see if they are preferable to singular isolates for DDT degradation, as R. pickettii produces biosurfactant, belonging to the major class of glycolipids-rhamnolipids (Plaza et al, 2007), which increases the solubility of DDT (Aislable et al, 1997) and further results in easy uptake of DDT by F. pinicola. In previous report, the adjunction of 10 mL R. pickettii heighten DDT degradation by the brown-rot fungus Daedalea dickinsii (Setyo et al, 2018), and also a consortium of R. pickettii with Pleurotus eryngii likewise was found to enhance DDT degradation (Purnomo et al, 2019a). Several studies have also shown fungus-bacterium co-culture degradation of pyrene, phenanthrene, and fluoranthene by 67%, compared to degradation by 39% by cultures of fungal and by 56% by cultures of bacterial, with an extended incubation period of 28 days (Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Mixed cultures have been inspected to see if they are preferable to singular isolates for DDT degradation, as R. pickettii produces biosurfactant, belonging to the major class of glycolipids-rhamnolipids (Plaza et al, 2007), which increases the solubility of DDT (Aislable et al, 1997) and further results in easy uptake of DDT by F. pinicola. In previous report, the adjunction of 10 mL R. pickettii heighten DDT degradation by the brown-rot fungus Daedalea dickinsii (Setyo et al, 2018), and also a consortium of R. pickettii with Pleurotus eryngii likewise was found to enhance DDT degradation (Purnomo et al, 2019a). Several studies have also shown fungus-bacterium co-culture degradation of pyrene, phenanthrene, and fluoranthene by 67%, compared to degradation by 39% by cultures of fungal and by 56% by cultures of bacterial, with an extended incubation period of 28 days (Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…The suspension was incubated for 7 days at 30 C, while the control cultures were annihilated by autoclave (121 C, 15 min) in after pre-incubation. The best combination of co-cultures for DDT degradation was recommended for further additional experiments (Purnomo, 2017;Purnomo et al, 2019a). For the establishment of the degradation pathway, DDT metabolites (DDE, DDD, and DDMU) were used as substrates.…”
Section: Ddt Degradation By Co-cultures Of F Pinicola and R Pickettiimentioning
confidence: 99%
“…The plate was incubated at 25°C in the dark. After day 4th of incubation, the mycelial growth was started to measure (Purnomo et al 2019a).…”
Section: Interaction Assay Of Fungal-bacteriamentioning
confidence: 99%
“…Biosurfactant-producing bacteria have increased the ability of fungi to degrade DDT in co-cultures. The co-cultures of P. eryngii and Ralstonia pickettii (Purnomo et al 2019a), P. ostreatus and Pseudomonas aeruginosa, P. ostreatus, and Bacillus subtilis (Purnomo et al 2017a), G. lingzhi and B. subtilis (Boelan and Purnomo 2018), G. lingzhi and P. aeruginosa (Boelan and Purnomo 2019), P. brevispora and B. subtilis (Purnomo and Fajriah 2017), Fomitopsis pinicola and B. subtilis (Sariwati et al 2017), F. pinicola and P. aeruginosa (Sariwati and Purnomo 2018), F. pinicola and R. pickettii (Purnomo et al 2020a), Daedalea dickinsii and R. pickettii (Setyo et al 2018) have been effective in degrading large amounts of DDT about 70-100%. Although some co-cultures of surfactant-producing bacteria and fungi were able to lessen large quantities of DDT, the metabolite compounds produced from the process still have high levels of toxicity such as DDE and DDD.…”
mentioning
confidence: 99%
“…Besides, B. subtilis can be mixed with some brown-rot fungi (BRF), such as Gloephyllum trabeum, Daedalea dickinsii, and Fomitopsis pinicola as well as white-rot fungi (WRF) such as Pleurotus ostreatus, Pleurotus eryngii, and Ganoderma lingzhi. Mixed culture B. subtilis and BRF had been reported to enhance DDT degradation as well as dyes decolorization [29][30][31][32].…”
Section: Analysis Of Degradation Products (Gc-ms)mentioning
confidence: 99%